Democratisation of Teaching and Learning: a tool for the implementation of the Tuning Approach in Higher Education? - Jane Iloanya (Universidad de Deusto, 2017)
Teaching and learning in Contemporary Higher Education is experiencing a change of paradigm in the approach used for curriculum design and instruction. This paper examines the application of democratisation of teaching and learning as a crucial tool for the implementation of the Tuning Approach in the teaching and learning processes in higher education. A qualitative research approach was used to collect information from two institutions of higher learning in Botswana. Findings from the study indicate, that, there are democratic elements in the teaching and learning processes as evidenced by the use of the learning -outcomes approach in lesson planning by the lecturers, and in the various ways students are engaged in teaching and learning processes. However, the study revealed that students are not fully involved in planning curriculum and workload.